2015
DOI: 10.14393/bj-v31n5a2015-26876
|View full text |Cite
|
Sign up to set email alerts
|

Spray deposition on coffee leaves from airblast sprayers with and without electrostatic charge

Abstract: ABSTRACT:Studies on the quality of applications of plant protection products on coffee crops are lacking. Thus, we studied spray deposition on coffee leaves and losses to the soil from hydropneumatic spraying at different spray volumes and with and without an electrostatic charge. The experiment was set up using randomized blocks in a factorial design (4 x 2 + 1). Spray deposition on the upper, middle and lower parts of the canopy and losses to the soil were evaluated using Brilliant Blue tracer. Applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…This result indicates that electrostatic spraying could achieve depositions similar to conventional spraying, but with 48% less volume, thus reducing the use of plant protection products and the risk of environmental contamination. These results are in line with studies carried out with electrostatic spraying in other crops, where deposition increases of the order of 0.5 to 2.5 times were quantified, compared to conventional spraying systems [23][24][25][26]33].…”
Section: Plant Canopy Depositionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result indicates that electrostatic spraying could achieve depositions similar to conventional spraying, but with 48% less volume, thus reducing the use of plant protection products and the risk of environmental contamination. These results are in line with studies carried out with electrostatic spraying in other crops, where deposition increases of the order of 0.5 to 2.5 times were quantified, compared to conventional spraying systems [23][24][25][26]33].…”
Section: Plant Canopy Depositionsupporting
confidence: 89%
“…In grapevines, different studies have been carried out in which an increase in the average deposition in the plant canopy was obtained [22,23], resulting in a potential reduction in the application volume of around 68% compared to conventional spraying, and more homogenous distribution of the plant protection product in the plant canopy [23]. Neto et al [24] studied spray deposition on coffee leaves and losses to the ground from hydropneumatic spraying at different spray volumes, both with and without an electrostatic charge; they found that electrostatic spraying resulted in greater deposition on the lower part of the crop and fewer losses to the ground. Patel et al [25] compared an electrostatic sprayer to different spraying equipment in a cotton crop, finding that the leaf coverage, droplet density, and biological effectiveness were better with the electrostatic spraying treatments than those carried out with the other equipment.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, because an electrostatic sprayer is usually adjusted to spray a lower volume rate than a mist-blower, the resulting treatment losses are reduced; moreover, it improves the homogeneity of distribution and product penetration in the vegetation (Laryea and No, 2003;Jahannama et al, 2005, Maski andDurairaj, 2010;Yang et al, 2015;Mermer et al, 2016, Patel et al, 2017. In addition, this technology is very versatile and has been previously applied to different types of crops (Arnold et al, 1984;Cayley et al, 1984;Abdelbagi and Adams, 1987;Western et al, 1994;Kabashima et al, 1995;Derksen et al, 2007;Gitirana Neto et al, 2015;Tourino et al, 2017;Tavares et al, 2017;Joseph and Bolda, 2018). Pascuzzi and Cerruto (2015) conducted field tests with an electrostatic sprayer in vineyards, finding that this could deliver greater deposits on leaves than a traditional air-assisted sprayer.…”
Section: Introductionmentioning
confidence: 99%
“…Airblast sprayers are typically used with an application rate of about 200-5000 l.ha -1 (Neto et al, 2015). Application rate throughout the application procedure is correlated with many factors.…”
Section: Agricultural Sprayer Design and Application Parametersmentioning
confidence: 99%